The role of shear conditions on floc characteristics and membrane fouling in coagulation/ultrafiltration hybrid process – the effect of flocculation duration and slow shear force. Issue 1 (21st December 2015) - Nan, Jun; Yao, Meng; Li, Qinggui; Zhan, Dan; Chen, Ting; Wang, Zhenbei; Li, Haoyu
Abstract : The impact of shear conditions during coagulation on the ultrafiltration permeate flux in a coagulation–ultrafiltration (C–UF) process was investigated. Abstract : The impact of shear conditions during coagulation on the ultrafiltration permeate flux in a coagulation–ultrafiltration (C–UF) process was investigated. Different flocculation durations and slow shear forces were used to determine the impact of shear conditions on the C–UF process. Floc characteristics, including the average size, fractal dimension and flocs size distribution under different coagulation conditions were studied. Moreover, the normalized flux and reversibility of membrane fouling were also analyzed to investigate membrane fouling. The results indicated that flocs formed at a shorter flocculation duration with small fractal dimensions and easily developed a cake layer with larger pores and a fluffy structure on the membrane surface. However, a higher frequency of small-sized flocs still remained at a flocculation time of 5 min, which was attributed to inadequate collision among particles, which could cause severe membrane fouling. As a result, slow stirring for an appropriately short time (10 min) and the reduction of low shear force ( G = 8 s −1 ) are conducive for forming flocs with a loose and porous structure without the occurrence of more small particles in water, which seemed to effectively improve the membrane permeability.